Creatine-electrolyte supplementation improves repeated sprint cycling performance: A double blind randomized control study. Issue 1 (2nd May 2018) - Crisafulli, Daniel L.; Buddhadev, Harsh H.; Brilla, Lorrie R.; Chalmers, Gordon R.; Suprak, David N.; San Juan, Jun G.
Abstract: Background: Creatine supplementation is recommended as an ergogenic aid to improve repeated sprint cycling performance. Furthermore, creatine uptake is increased in the presence of electrolytes. Prior research examining the effect of a creatine-electrolyte (CE) supplement on repeated sprint cycling performance, however, did not show post-supplementation improvement. The purpose of this double blind randomized control study was to investigate the effect of a six-week CE supplementation intervention on overall and repeated peak and mean power output during repeated cycling sprints with recovery periods of 2 min between sprints. Methods: Peak and mean power generated by 23 male recreational cyclists (CE group: n = 12; 24.0 ± 4.2 years; placebo (P) group: n = 11; 23.3 ± 3.1 years) were measured on a Velotron ergometer as they completed five 15-s cycling sprints, with 2 min of recovery between sprints, pre- and post-supplementation. Mixed-model ANOVAs were used for statistical analyses. Results: A supplement-time interaction showed a 4% increase in overall peak power (pre: 734 ± 75 W; post: 765 ± 71 W; p = 0.040; ηp 2 = 0.187) and a 5% increase in overall mean power (pre: 586 ± 72 W; post: 615 ± 74 W; p = 0.019; ηp 2 = 0.234) from pre- to post-supplementation for the CE group. For the P group, no differences were observed in overall peak (pre: 768 ± 95 W; post: 772 ± 108 W; p = 0.735) and overall mean power (pre: 638 ± 77 W; post: 643 ± 92 W; p = 0.435) from pre- to post-testing. For repeated sprint analysis, peak (pre: 737 ± 88 W; post: 767 ± 92 W; p = 0.002; ηp 2 = 0.380) and mean (pre: 650 ± 92 W; post: 694 ± 87 W; p < 0.001; ηp 2 = 0.578) power output were significantly increased only in the first sprint effort in CE group from pre- to post-supplementation testing. For the P group, no differences were observed for repeated sprint performance. Conclusion: A CE supplement improves overall and repeated short duration sprint cycling performance when sprints are interspersed with adequate recovery periods.